2023
DOI: 10.3390/molecules28083610
|View full text |Cite
|
Sign up to set email alerts
|

The Research Progress of Extraction, Purification and Analysis Methods of Phenolic Compounds from Blueberry: A Comprehensive Review

Abstract: Blueberry is the source of a variety of bioactive substances, including phenolic compounds, such as anthocyanins, pterostilbene, phenolic acids, etc. Several studies have revealed that polyphenols in blueberry have important bioactivities in maintaining health, such as antioxidant and anti-tumor activities, immune regulation, the prevention of chronic diseases, etc. Therefore, these phenolic compounds in blueberries have been widely used in the field of healthcare, and the extraction, isolation, and purificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 114 publications
0
6
0
Order By: Relevance
“…It seems reasonable to think that the ABTS radical may have an affinity for other families of non-phenolic compounds, hence its lower significance in the correlation with antioxidant activity [29,43,44]. Figure 6 shows the results of the sensory analysis carried out, in which the organoleptic quality parameters such as color, aroma, and flavor were evaluated using the following evaluation criteria and scores: undesirable (1-2), acceptable (3-4), and desirable (5)(6). Figure 6A shows the scores given by the three expert tasters, who concluded that, in aroma, the best wine was the one made from the fresh grapes and the dried blueberries (M 1 ) and inoculated with M05 Mead yeast (W 1 M).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems reasonable to think that the ABTS radical may have an affinity for other families of non-phenolic compounds, hence its lower significance in the correlation with antioxidant activity [29,43,44]. Figure 6 shows the results of the sensory analysis carried out, in which the organoleptic quality parameters such as color, aroma, and flavor were evaluated using the following evaluation criteria and scores: undesirable (1-2), acceptable (3-4), and desirable (5)(6). Figure 6A shows the scores given by the three expert tasters, who concluded that, in aroma, the best wine was the one made from the fresh grapes and the dried blueberries (M 1 ) and inoculated with M05 Mead yeast (W 1 M).…”
Section: Resultsmentioning
confidence: 99%
“…Red grapes and blueberries are known for their high content of bioactive compounds and antioxidant activity due to their skin or pulp color [1][2][3]. These characteristics give them, among other fruits [4][5][6], numerous beneficial health properties, such as their anticancer, anti-inflammatory, and antimicrobial capacity. The presence of antioxidants in these fruits is particularly important as they can react with reactive oxygen species (ROS), which are unstable and highly reactive molecules present in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…The same authors implied that blueberries contain a large number of phytochemicals, and most of them are anthocyanin pigments. Blueberries are rich in endogenous phenols, which are the most beneficial components in blueberries and include anthocyanins, tannins, pterostilbene and phenolic acids and are utilized as natural colorants and preservatives in foods [8]. As the most abundant compound, various anthocyanins compounds up to fifteen different ones such as monoarabinosides, monoglucosides and monogalactosides of cyanidin, peonidin, delphinidin, petunidin and malvidin previously reported in blueberries by the several authors [9] [10] [11].…”
Section: Health Promoting Propertiesmentioning
confidence: 99%
“…Due to having rich nutritional content, blueberry has been developed into many nutritional supplements for disease prevention and dietary regulation, such as blueberry lutein eye care tablets, blueberry dietary supplements as blueberry powder, pterostilbene capsules e.g. Because of its great importance some of the authors reviewed on the progress of extraction, purification and analysis methods of phenolic compounds from blueberry, recently [8].…”
Section: Health Promoting Propertiesmentioning
confidence: 99%
“…To determine the anthocyanins in the different organs of purple corn, the solvent extraction method mentioned by Tan and Bai et al [47,48] was adopted and improved. The extraction agent was a mixture of ethanol and hydrochloric acid (95% ethanol and 1.5 mol/L hydrochloric acid, volume ratio of 85:15).…”
Section: Extraction and Quantification Of Anthocyaninmentioning
confidence: 99%